The crosstalk between hematopoietic stem cells and their niches. Issue 4 (July 2018) - Durand, Charles; Charbord, Pierre; Jaffredo, Thierry
Abstract : Purpose of review: Hematopoietic stem cells (HSCs) reside in specific microenvironments also called niches that regulate HSC functions. Understanding the molecular and cellular mechanisms involved in the crosstalk between HSCs and niche cells is a major issue in stem cell biology and regenerative medicine. The purpose of this review is to discuss recent advances in this field with particular emphasis on the transcriptional landscape of HSC niche cells and the roles of extracellular vesicles (EVs) in the dialog between HSCs and their microenvironments. Recent findings: The development of high-throughput technologies combined with computational methods has considerably improved our knowledge on the molecular identity of HSC niche cells. Accumulating evidence strongly suggest that the dialog between HSCs and their niches is bidirectional and that EVs play an important role in this process. Summary: These advances bring a unique conceptual and methodological framework for understanding the molecular complexity of the HSC niche and identifying novel HSC regulators. They are also promising for exploring the reciprocal influence of HSCs on niche cells and delivering specific molecules to HSCs in regenerative medicine.